ANALISIS IMPLEMENTASI PENGUKURAN KINERJA BERBASIS BALANCED SCORECARD - Rahmanto, Basuki Toto; Karen, Ester (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this research is to analyze the implementation of performance measurement based on a balaced scorecard for government agencies with a case study on KPP Jakarta Pasar Rebo. This study was a descriptive-quantitative research through case studies with quantitative methods. The data used are primary data from the results of a questionnaire given to all taxpayers in KPP Pratama Jakarta Pasar Rebo and secondary data from the documentation. The results obtained from this study showed the performance measurement using the balanced scorecard for all three perspectives: customer satisfaction, internal business process and learning and growth as a whole obtain good results with some suggestions and improvements that need to be done, but on the financial perspective showing results unfavorable. Keywords: balance scorecard, performance